Mosasaurs from Germany – a brief history of the first 100 years of research. Issue 1 (21st July 2014) - Sachs, Sven; Hornung, Jahn J.; Reich, Mike
Abstract: In Germany, mosasaur remains are very rare and only incompletely known. However, the earliest records date back to the 1830s, when tooth crowns were found in the chalk of the Isle of Rügen. A number of prominent figures in German palaeontology and geosciences of the 19th and 20th centuries focused on these remains, including, among others, Friedrich von Hagenow, Hermann von Meyer, Andreas Wagner, Hanns Bruno Geinitz and Josef Pompeckj. Most of these works were only short notes, given the scant material. However, the discovery of fragmentary cranial remains in Westphalia in 1908 led to a more comprehensive discussion, which is also of historical importance, as it illustrates the discussions on the highly controversial and radical universal phylogenetic theory proposed by Gustav Steinmann in 1908. This theory saw the existence of continuous lines of descent, evolving in parallel, and did not regard higher taxonomic units as monophyletic groups but as intermediate paraphyletic stages of evolution. In this idea, nearly all fossil taxa form part of these lineages, which extend into the present time, and natural extinction occurs very rarely, if ever. In Steinmann's concept, mosasaurs were not closely related to squamates but formed an intermediate member in a anagenetic chain from Triassic thalattosaurs to extant baleen whales. The newly found specimen led Josef Pompeckj to write a vehement rebuttal to Steinmann's theory, published in 1910, showing that his conclusions were conjectural and speculative, being based on convergence and not supported by scientific evidence. This particular specimen, housed in Göttingen, later also inspired a piece of palaeoart by Franz Roubal under the instructions of Othenio Abel. With the exception of a vertebra from the Campanian of former East Prussia (now Russian Federation), and a possible vertebra from the Cenomanian of Dresden, Saxony, all datable material – today partly lost – originated from the northern part of present-day Germany and stratigraphically from the Campanian–Maastrichtian. The purported record from the Cenomanian of Bavaria (southeastern Germany) was most probably an error, based on Upper Jurassic crocodilian material.